Pilot-scale study based on integrated fixed-film activated sludge process for cement industrial wastewater treatment - Mohamed Nabil Ali; Hanan A. Fouad; Mohamed M. Meky; Rehab M. Elhefny (Journal of Degraded and Mining Lands Management, 2021)
Due to the lack of freshwater resources in Egypt, cement wastewater treatment was performed to widen the range of the water used in irrigation to face the massive future water scarcity. In this study, integrated fixed-film activated sludge (IFAS) was used as a biological treatment method. A laboratory pilot was established as a simulation of the IFAS process. The scale-pilot consists of a primary sedimentation tank, an IFAS tank equipped with an air blower, and a final settling tank. Three experimental attempts were performed using 3 different bio-carriers. In the first trial, Luffa sponges were used as natural bio-carriers and polyurethane sponges (PU) as artificial bio-carriers in the second trial, in addition to a combination between Luffa and PU sponges as a hybrid bio-carrier in the third trial. After analyzing the physicochemical properties of wastewater at the national research center in Cairo, the removal efficiency of TSS (total suspended solids), COD (chemical oxygen demand) , BOD(biological oxygen demand), TN (total nitrogen), and TP (total phosphorous) was 94.5%, 87.8%, 90.8%, 75.9%, and 69.4%, respectively in case of using the combination between Luffa and PU sponges. It can be concluded that using IFAS process was effective for cement wastewater treatment and the effluent wastewater met the Egyptian code limitations for reuse in agriculture purposes.